Human factors in the training of pilots - Koonce, Jefferson M. (Taylor & Francis, 2002)
In this educational yet entertaining text, Jeff Koonce draws on his 44 years of pilot experience and 31 years as a professor of psychology and human factors engineering in addressing the questions of how to apply sound human factors principles to the training of pilots and to one's personal flying. The author discusses principles of human factors, and how they can be utilized in pilot training and evaluation. With a conversational tone, he also relates anecdotes, jokes, and truisms collected during his time as a flight instructor. He takes a positive approach to the subject, focusing on safety and good practice rather than on accidents. While problem areas are acknowledged, and the book points out how certain problems may result in mishaps, the author avoids focusing on individual accidents. Human Factors in the Training of Pilots is a must for pilots wanting to make a systematic study of the human factors issues behind safe flying, and for instructors or serious students needing an authoritative text.